2022
DOI: 10.1002/edm2.349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between D‐dimer levels in diabetic and non‐diabetic positive COVID‐19 adult patients: A hospital‐based study

Abstract: Background: Diabetes is one of the most common associated comorbidity with severe acute respiratory syndrome coronavirus (SARS-CoV-2) pneumonia patients.Coagulation disorders with D-dimer levels are increased in both diseases. This study aimed to compare the levels of D-dimer in DM and non-DM patients with coronavirus disease (COVID-19) and correlate it with the disease severity. Methods: This is a cross-sectional hospital-based study. It was conducted at royal care hospital, isolation COVID-19 Centre in 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The data analyzed by SPSS (Statistical Package for the Social Sciences) version 26, Categorical variables were described as frequency rates and percentages, and continuous variables were described using mean and Pearson Correlation(R), qui Squair, P-Value. The obtained results in a table (6 ) prove that correlation between D. Dimer, the table noted that there is a relationship between D Dimer and Age and chronic diseases, p-value < & = 0.05, and there is not a significant relationship between D Dimer and Type of infection and gender p-value < 0.05. 556 Patients' cases were collected from private and governmental laboratories, isolation and health care centers in the Derna, Al-Qubba City, and its surrounding areas.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The data analyzed by SPSS (Statistical Package for the Social Sciences) version 26, Categorical variables were described as frequency rates and percentages, and continuous variables were described using mean and Pearson Correlation(R), qui Squair, P-Value. The obtained results in a table (6 ) prove that correlation between D. Dimer, the table noted that there is a relationship between D Dimer and Age and chronic diseases, p-value < & = 0.05, and there is not a significant relationship between D Dimer and Type of infection and gender p-value < 0.05. 556 Patients' cases were collected from private and governmental laboratories, isolation and health care centers in the Derna, Al-Qubba City, and its surrounding areas.…”
Section: Discussionsupporting
confidence: 50%
“…Figure (5) The Figure illustrates the relationship between D. Dimer Result and Chronic Disease that the blood pressure was the highest followed by pneumonia, diabetes Miletus, Anemia, kidney disease, and Heart disease. It is apparent from the results in figure (6) that The Relationship between D. Dimer Result and Gender is that males have higher results than females. The obtained results in table (6) prove that correlation between D. Dimer, the table noted that there is a relationship between D Dimer and Age & chronic diseases, p-value < & = 0.05, and there is not a significant relationship between D Dimer and Type of infection and gender p-value < 0.05.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, it has been reported that the high D-dimer level in diabetic patients is significantly associated with COVID-19 severity. 30,31 Regarding neutrophil level, our results found a significant difference among the categorical groups (i.e., patients with a normal neutrophil count, neutropenia and neutrophilia) in terms of age (p < 0.001), 25(OH)D (p = 0.012), CRP (p < 0.001), ESR (p < 0.001), D-dimer (p < 0.001) and ferritin (p < 0.001). Thus, we then investigated whether there is a relationship between change in neutrophil count and age, inflammatory markers (i.e., CRP, ESR and ferritin), thrombotic marker (i.e., D-dimer) and 25(OH)D. Expectedly, it was found that age, inflammatory markers (i.e., CRP, ESR and ferritin) and thrombotic marker (i.e., D-dimer) were all significantly and positively correlated with the change in ANC (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%